Butterfly star in Taurus: Structures of young stellar objects - Lucas, P; Roche, P (1997)
We present high-resolution, near-infrared images of a sample of five low-mass young stellar objects in the Taurus-Auriga dark cloud, mostly observed with the 'shift and add' technique, together with deep polarimetric images. These systems are at the 'Class I' phase of evolution, prior to the T Tauri phase. Monte Carlo models tailored to the individual sources support the view that the flux distribution of the circumstellar nebulosity arises from an envelope with a bipolar cavity, but show that dust in outflows can also be prominent in the near-infrared. The source IRAS 04302 + 2247 is analysed in detail, since it displays a unique quadrupolar morphology, which is explained in terms of a system oriented precisely edge-on with a perpendicular outflow. The masses of the envelopes derived from the models are in good agreement with estimates obtained from submillimetre thermal fluxes and estimates derived from CS(J = 2 - 1) emission. Constraints are placed on envelope and cavity structure, indicating higher density near the equatorial plane, smooth, continuous density profiles and physically thin inner discs. Three of the five systems show evidence for two bipolar cavity/outflow systems, perhaps indicating that these are close binaries. The very high (up to 80 per cent) degrees of polarization observed in the envelopes show that the scattering is dominated by small, interstellar-type dust grains, and the morphologies and high polarizations of the cores show that the protostars themselves are usually obscured at this phase of evolution, even at 3.7 μm. © 1997 RAS.